2014
DOI: 10.17221/49/2014-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Douglas-fir (Pseudotsuga menziesii [Mirb.] Franco) on understorey layer species diversity in managed forests

Abstract: ABSTRACT:In total, 67 parallel plots were chosen from the database of 153 phytosociological relevés made in the Douglas-fir and parallel Norway spruce, European Beech and oak-dominated stands to find influences of this introduced tree species on the understorey layer in totally 12 localities in the whole Czech Republic territory. Douglas-fir stands influence their habitats, which was indicated by species composition changes in the ground vegetation, as well as by abundance and dominance of particular species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 20 publications
4
20
0
1
Order By: Relevance
“…Afforestation of agricultural lands constitutes a serious change in soil dynamics, including soil structure, organic matter and nutrient dynamics [11][12][13][14]. Compared to Norway spruce, Douglas fir shows less negative effects on the forest soil [15,16] and herb vegetation layer [17], and thus Douglas fir can represent a very convenient substitute for declining spruce, at least as a part of its non-native range in commercial forests [18]. Douglas fir also appears promising under local conditions in terms of wood quality [19].…”
Section: Introductionmentioning
confidence: 99%
“…Afforestation of agricultural lands constitutes a serious change in soil dynamics, including soil structure, organic matter and nutrient dynamics [11][12][13][14]. Compared to Norway spruce, Douglas fir shows less negative effects on the forest soil [15,16] and herb vegetation layer [17], and thus Douglas fir can represent a very convenient substitute for declining spruce, at least as a part of its non-native range in commercial forests [18]. Douglas fir also appears promising under local conditions in terms of wood quality [19].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the content, abundance and cover of understory species depends on the species of trees present in the overstory. Namely, plants in the herbaceous layer are affected by the tree layer, which modifies the transmittance of light, the water balance and microclimate, litter characteristics, chemical characteristics and porosity of the soil, as well as through leaching of toxic compounds [1,5,11,35,39,50]. In addition, silvicultural management, former land use and atmospheric deposition have significant impact [1].…”
Section: Floristic Compositionmentioning
confidence: 99%
“…We also observed the presence of young beech in the Douglas fir culture, which is a sign that artificial stands of conifers are rejuvenated by beech, i.e., succession moves toward autochthonous forest vegetation [39]. On the other hand, in a study at 12 localities in the Czech Republic, it was established that the cultivation of Douglas fir was reflected in an increase in diversity, but also in a decrease in the abundance of ground vegetation at the sites [35]. The impact of Douglas fir was most pronounced in comparison to managed Norway spruce stands.…”
Section: Floristic Compositionmentioning
confidence: 99%
See 2 more Smart Citations